Experimental Verification of The Modified PSA Algorithm - Li, Xiao; Wang, Liqiang; Munochiveyi, Munyaradzi (IEEE access, 2022)
Being abundant and non-polluted, solar energy is an increasingly desirable energy source. Growing research is concerned about maximum solar energy acquisition from solar panels, especially in the automatic sun-tracking of the solar panels. This paper presents a modified algorithm based on the "PSA Algorithm" proposed in the 2001. And presents a new automatic solar tracking system with a two-axis is designed based on the algorithm. The PSA modified algorithm is used to calculate the sun's horizontal azimuth and zenith angle combined with time, longitude, latitude, and other information. We designed a prototype mainly composed of a microcontroller, a Global Positioning System (GPS) module, a digital compass, a tilt sensor, a 555 timer, and gates, optical couples, an H-bridge and two stepper motors. Then using the proposed prototype, a series of experiments are conducted in Tianjin City. Measured zenith angle values were collected and recorded based on the PSA modified algorithm and the original PSA algorithm, compared with the actual Zenith Angle of the Sun in Tianjin City. The comparison curves of Zenith Angle show that the measurement accuracy of the modified PSA algorithm is higher than that of the PSA original algorithm.